2017
DOI: 10.1177/2167702617699277
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Volume as an Amplifier of the Effect of Social Context on Adolescent Depression

Abstract: Recent models have focused on how brain-based individual differences in social sensitivity shape affective development in adolescence, when rates of depression escalate. Given the importance of the hippocampus in binding contextual and affective elements of experience, as well as its putative role in depression, we examined hippocampal volume as a moderator of the effects of social context on depressive symptoms in a sample of 209 Mexican-origin adolescents. Adolescents with larger versus smaller hippocampal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 110 publications
6
43
0
Order By: Relevance
“…In their longitudinal study of adolescents from, on average, 12 to 14 y of age, Whittle et al (55) found laboratory-assessed maternal aggression predictive of depressive symptoms, specifically among girls with comparatively large bilateral hippocampi. In addition, in their study of older adolescents, Schriber et al (41) observed depression both negatively related to family connectedness and positively related to community crime, specifically among adolescents with larger left hippocampi. Similar to our current findings, Schriber et al (41) did not observe a moderating influence of right hippocampal volume.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In their longitudinal study of adolescents from, on average, 12 to 14 y of age, Whittle et al (55) found laboratory-assessed maternal aggression predictive of depressive symptoms, specifically among girls with comparatively large bilateral hippocampi. In addition, in their study of older adolescents, Schriber et al (41) observed depression both negatively related to family connectedness and positively related to community crime, specifically among adolescents with larger left hippocampi. Similar to our current findings, Schriber et al (41) did not observe a moderating influence of right hippocampal volume.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, in their study of older adolescents, Schriber et al (41) observed depression both negatively related to family connectedness and positively related to community crime, specifically among adolescents with larger left hippocampi. Similar to our current findings, Schriber et al (41) did not observe a moderating influence of right hippocampal volume.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Initially, participants were recruited when they were in fifth grade, drawn at random in two cohorts from school rosters during the 2006–2007 and 2007–2008 school years. About 6 years later, 229 participants (119 males and 110 females) were recruited into a substudy designed to examine neurobiological mechanisms in the etiology of depression (Schriber et al, ; Schriber et al, ; Weissman, Gelardi, et al, ; Weissman, Guyer, Ferrer, Robins, & Hastings, ). Youth with elevated depressive symptoms were oversampled from the CFP parent sample, using counts of adolescents' self‐reported symptoms in ninth grade (Age 14) on the Diagnostic Interview Schedule for Children‐IV (Shaffer, Fisher, Lucas, Dulcan, & Schwab‐Stone, ) and indicators of elevated severity from the Anhedonic Depression and General Distress subscales of the Mood and Anxiety Symptom Questionnaire (Watson & Clark, ).…”
Section: Methodsmentioning
confidence: 99%